simplify the following equation using boolean laws and rules:

x=~(A(+)B) + ~(AB)+~((A(+)B)AC)+(~A)C

(+) means plus in the circle
~ means not

Do you get

~A + ~B + ~C

?

i got two things to say:

1) how did you get ~A + ~B + ~C
2) my friend of mines got ~(ABC) for this exact question, is my friend correct?

The two are equivalent.

how did the other Anonymous get ~A + ~B + ~C

To simplify the given equation using Boolean laws and rules, we will apply various logic operations and simplifications step by step. Let's break down the given equation:

x = ~(A(+)B) + ~(AB) + ~((A(+)B)AC) + (~A)C

Step 1: Apply the De Morgan's Laws
De Morgan's Laws state:
- ~(A + B) = ~A * ~B (1)
- ~(A * B) = ~A + ~B (2)

Using equation (1), simplify the first term ~(A(+)B):
~(A(+)B) = ~A * ~B

x = ~A * ~B + ~(AB) + ~((A(+)B)AC) + (~A)C

Step 2: Apply De Morgan's Laws again
Using equation (2), simplify the second term ~(AB):
~(AB) = ~A + ~B

x = ~A * ~B + (~A + ~B) + ~((A(+)B)AC) + (~A)C

Step 3: Distribute the negation ~(A(+)B)AC
~((A(+)B)AC) = ~(A(+)B) * ~A * ~C

x = ~A * ~B + (~A + ~B) + ~(A(+)B) * ~A * ~C + (~A)C

Step 4: Distribute the negation ~(A(+)B) * ~A * ~C
~(A(+)B) * ~A * ~C = (~A * ~B) * ~A * ~C

x = ~A * ~B + (~A + ~B) + (~A * ~B) * ~A * ~C + (~A)C

Step 5: Apply the idempotent law
In Boolean algebra, the idempotent law states that:
- X + X = X
- X * X = X

Apply the idempotent law to simplify the equation further:

x = ~A * ~B + ~A + ~B + (~A * ~B) * ~A * ~C + (~A)C

Step 6: Apply the distributive law
The distributive law states that:
- X * (Y + Z) = X * Y + X * Z
- X + (Y * Z) = (X + Y) * (X + Z)

Apply the distributive law to simplify the equation:

x = ~A * (~B + 1) + ~B + (~A * ~B) * ~A * ~C + (~A)C

Since ~B + 1 = 1 (complement law), and ~A * ~B * ~A = 0 (one of the variables is complemented), we can further simplify:

x = ~A + ~B + 0 * ~C + (~A)C

Step 7: Simplify the zero and identity operations
- 0 * X = 0
- X + 0 = X

Applying these simplifications:

x = ~A + ~B + 0 + (~A)C

Step 8: Simplify the equation further
- 0 + X = X

Applying this simplification:

x = ~A + ~B + (~A)C

Therefore, the simplified equation is x = ~A + ~B + (~A)C.